Analisis Kebutuhan Media Pembelajaran Quiziz Pada Materi Peradilan Islam Dan Hikmahnya - dian nur hikmah; Fadhila Herniyanti, Nor (Universitas Majalengka, 2024)
This research focuses on the development of technology-based teaching media, namely Quizizz, in learning Islamic Justice material and its wisdom in class XI MA Darul Amin Palangka Raya. Technology has the potential to improve the quality of learning when applied appropriately. Although the majority of students (58.3%) feel that they do not need this technology-based media, there are 41.7% of students who feel that the use of Quizizz can support their learning process. Factors that affect student disinterest include differences in learning styles, lack of familiarity with technology, and limited access. On the other hand, students who support the use of Quizizz consider it an interactive, fun, and flexible learning medium that allows independent and flexible learning. This study uses a quantitative descriptive method to measure students' needs and perceptions of the use of Quizizz. Data collection techniques are carried out through interviews, observations, and documentation. The results of the study show that this technology-based teaching medium can help increase.